Assessing Work Addiction: Validity of the Italian Version of the Work Addiction Risk Test - Marcatto, Francesco; Di Blas, Lisa; Ferrante, Donatella; Festa, Simone; Palomba, Ilaria; Larese Filon, Francesca (La Medicina del Lavoro, 2025)
Background: Work addiction is a contemporary addiction affecting 8.3% to 22% of individuals in Europe, leading to detrimental effects on relationships, work-family balance, and overall well-being. Given its prevalence and impact, standardized assessment tools are crucial for distinguishing between work addiction and healthy work engagement. Methods: This study evaluated the psychometric properties of the Italian version of the Work Addiction Risk Test (WART). A convenience sample of 700 workers from Northeastern and Southern Italy completed the Italian version of the WART  along with other well-being at work and personality measures. Results:Exploratory factor analysis revealed a five-factor structure of the WART, partially overlapping with the original version. Despite some weaknesses in the factor structure, the WART demonstrated satisfactory psychometric properties, including internal consistency and associations with organizational and personality correlates of work addiction. Conclusions: The Italian version of the WART is a reliable tool for assessing work addiction risk among Italian workers. This tool can aid in identifying individuals at risk and facilitating early intervention and support. Future research should focus on further validating the factor structure and exploring the utility of the WART indifferent cultural and occupational contexts.